2018
DOI: 10.6026/97320630014488
|View full text |Cite
|
Sign up to set email alerts
|

Identification and prioritization of macrolideresistance genes with hypothetical annotation in Streptococcus pneumoniae

Abstract: Macrolide resistant Streptococcus pneumoniae infections have limited treatment options. While some resistance mechanisms are well established, ample understanding is limited by incomplete genome annotation (hypothetical genes). Some hypothetical genes encode a domain of unknown function (DUF), a conserved protein domain with uncharacterized function. Here, we identify and confirm macrolide resistance genes. We further explore DUFs from macrolide resistance hypothetical genes to prioritize them for experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…To overcome these limitations, GSEA considers all genes during analysis by removing the need for a statistical cut-off ( Tipney and Hunter, 2010 ). GSEA is extremely complex, and best for advanced educational projects such as a Master thesis, where the goal is to identify true HPs whose immediate experimental examination could directly enhance scientific understanding of a variety of biological mechanisms ( Goad and Harris, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome these limitations, GSEA considers all genes during analysis by removing the need for a statistical cut-off ( Tipney and Hunter, 2010 ). GSEA is extremely complex, and best for advanced educational projects such as a Master thesis, where the goal is to identify true HPs whose immediate experimental examination could directly enhance scientific understanding of a variety of biological mechanisms ( Goad and Harris, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…If more than two experimental groups are available, HPs can be selected by gene enrichment analysis ( Goad and Harris, 2018 ). HPs can be selected by either singular enrichment analysis or gene set enrichment analysis ( Huang et al, 2009 ; Tipney and Hunter, 2010 ).…”
Section: Hypothetical Protein Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prior study to identify novel genes associated with macrolide resistance in Streptococcus pneumoniae , we demonstrated a GSEA-approach for gene identification that compared differential gene expression between mRNA expression datasets (Goad and Harris, 2018). This study successfully identified known and novel genes though it was limited due to incomplete genome annotation, a common problem for many microbial genomes (Kolker et al, 2004; Sivashankari and Shanmughavel, 2006; Mohan and Venugopal, 2012; Bharat Siva Varma et al, 2015; Ijaq et al, 2015; Islam et al, 2015; School et al, 2016; Omeershffudin and Kumar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a prior study to identify genes associated with macrolide resistance in Streptococcus pneumoniae, we demonstrated a GSEA-approach for gene identification that compared differential gene expression between mRNA expression datasets [42]. This study successfully identified known and novel genes though it was limited due to incomplete genome annotation, a common problem for many microbial genomes [43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%